Electrolytes based on primary ammonium salts as ionic liquids for PEMFC-membranes - Hanna, Maha (Array, 2009)
Summary: Physico-chemical characterization of a series of salts prepared from primary amines was performed in order to obtain the salts as protonic ionic liquids (PILs). It was shown that the majority of these salts are thermally stable up to 400 °C, while the melting point of each salt depends on the nature of the anion and amine substitutions. The results of cyclic voltammetry experiments showed that the amines and the salts (HNR3+, A–) could be oxidized only at very high potentials (> 1.9 V/SHE) which is compatible with their use in PEM fuel cells. Conductivities of salts at 130 °C are between 0.01 and 13 mS cm–1. The best conductivity was observed for the salt resulting from asymmetric amines/trifluoromethanesulfonic acid association. Incorporation of these compounds within Nafion® has also been studied, particularly with respect to the compatibility of PIL/Nafion® and conductivity of these newly formed membranes